Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1038/ncomms3219
|View full text |Cite
|
Sign up to set email alerts
|

Group A PP2Cs evolved in land plants as key regulators of intrinsic desiccation tolerance

Abstract: Vegetative desiccation tolerance is common in bryophytes, although this character has been lost in most vascular plants. The moss Physcomitrella patens survives complete desiccation if treated with abscisic acid (ABA). Group A protein phosphatases type 2C (PP2C) are negative regulators of abscisic acid signalling. Here we show that the elimination of Group A PP2C is sufficient to ensure P. patens survival to full desiccation, without ABA treatment, although its growth is severely hindered. Microarray analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
117
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 116 publications
(121 citation statements)
references
References 59 publications
4
117
0
Order By: Relevance
“…ABA-induced activation of the protein kinase corresponding to the expected size of SnRK2 (39 kDa) has been demonstrated recently in P. patens protonemata by in-gel kinase assays using histone IIIS as a substrate (20). We found that protonemata of The protonemata of the lines used in B were bombarded with the Em-GUS and Ubi-LUC constructs and incubated with or without 10 μM ABA for 1 d, followed by the GUS and LUC assays.…”
Section: Resultssupporting
confidence: 51%
See 3 more Smart Citations
“…ABA-induced activation of the protein kinase corresponding to the expected size of SnRK2 (39 kDa) has been demonstrated recently in P. patens protonemata by in-gel kinase assays using histone IIIS as a substrate (20). We found that protonemata of The protonemata of the lines used in B were bombarded with the Em-GUS and Ubi-LUC constructs and incubated with or without 10 μM ABA for 1 d, followed by the GUS and LUC assays.…”
Section: Resultssupporting
confidence: 51%
“…Transcriptome Analysis. Microarray analysis was carried out using a P. patens custom oligonucleotide microarray in which 33,942 gene-specific probes were mounted in an Agilent format microarray as described previously (20). Protonemata of the WT line and AR7 cultured on normal BCDAT medium or medium containing 10 μM ABA for 6 h were used for RNA extraction.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…P. patens is dehydrationtolerant but can become desiccation-and freezing-tolerant by pre-treatment with ABA (Khandelwal et al 2010;Nagao et al 2005). Whereas abiotic stress signaling seems largely conserved between mosses and flowering plants (Khandelwal et al 2010;Komatsu et al 2013;Richardt et al 2010), several studies report on so-called orphan, non-characterized stress responsive moss genes and proteins (Beike et al 2015b;Cui et al 2012).…”
Section: Mosses Employ Several Strategies To Increase Stress Tolerancementioning
confidence: 99%